2007
DOI: 10.1063/1.2804566
|View full text |Cite
|
Sign up to set email alerts
|

ZnO-based thin film transistors having high refractive index silicon nitride gate

Abstract: Articles you may be interested inHigh carrier mobility and electrical stability under negative bias illumination stress of ZnO thin-film transistors with N2O plasma treated HfOx gate dielectrics High performance thin film transistor with cosputtered amorphous Zn-In-Sn-O channel: Combinatorial approach Appl. Phys. Lett. 95, 072104 (2009); 10.1063/1.3206948 Effects of oxygen contents in the active channel layer on electrical characteristics of ZnO-based thin film transistors J.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Silicon nitride is a promising material to be used as an insulating matrix in metal/ceramic granular systems and multilayers, since it has been found to be a good candidate for applications in electronic devices due to its optical and transport properties, as well as for its chemical inertness at high temperatures. [15][16][17] We have observed that TM films and particles embedded in a Si 3 N 4 matrix display substantial differences in their magnetic properties. For Ni/Si 3 N 4 , the presence of an interlayer formed by nickel nitride with a rock salt cubic geometry results in a diminution of the magnetic signal of the samples.…”
Section: Introductionmentioning
confidence: 94%
“…Silicon nitride is a promising material to be used as an insulating matrix in metal/ceramic granular systems and multilayers, since it has been found to be a good candidate for applications in electronic devices due to its optical and transport properties, as well as for its chemical inertness at high temperatures. [15][16][17] We have observed that TM films and particles embedded in a Si 3 N 4 matrix display substantial differences in their magnetic properties. For Ni/Si 3 N 4 , the presence of an interlayer formed by nickel nitride with a rock salt cubic geometry results in a diminution of the magnetic signal of the samples.…”
Section: Introductionmentioning
confidence: 94%
“…ZnO-based thin film transistors (TFTs) have attracted considerable attention, because of their superior properties that include wide band gap, transparency, and high field effect mobility compared to that of the conventional a-Si TFTs [1][2][3][4][5][6][7][8]. Recent advances in the use of various channel layers with proper materials have contributed to solving problems associated with conventional Sibased TFTs such as their low field effect mobility and opacity.…”
Section: Introductionmentioning
confidence: 99%
“…2 There are several reasons that make ZnO an attractive choice as a semiconductor active layer in thin-film transistors: low cost, stability, low processing temperature, stability under visible light due to its wide band gap (3.4 eV), and excellent electrical properties such as tunable electrical conductivity. 3 When used as the active channel layer in TFTs, the deposition parameters of ZnO can be optimized to achieve high mobility, [4][5][6][7][8][9] low threshold voltage, 4 and high current ratios (I on / I off ). 6,10 The channel mobility is directly related with the crystalline quality of the semiconductor active layer, and it can be improved by employing epitaxial deposition techniques 8,9 and/or by postdeposition annealing treatment.…”
Section: Introductionmentioning
confidence: 99%
“…3 When used as the active channel layer in TFTs, the deposition parameters of ZnO can be optimized to achieve high mobility, [4][5][6][7][8][9] low threshold voltage, 4 and high current ratios (I on / I off ). 6,10 The channel mobility is directly related with the crystalline quality of the semiconductor active layer, and it can be improved by employing epitaxial deposition techniques 8,9 and/or by postdeposition annealing treatment. 7 Zinc oxide thin films have been fabricated using several deposition techniques such as chemical vapor deposition (CVD), 11 pulsed laser deposition (PLD), 12 spin coating, 13 atomic layer deposition (ALD), 14 laser molecular-beam epitaxy (L-MBE), 8,9 and radiofrequency (RF) magnetron sputtering.…”
Section: Introductionmentioning
confidence: 99%